Role of the government in certain circumstances - Klaric, Mirko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The role of state administration and its public institutions in certain circumstances represents one of the most significant issues in the last twenty years following the serious security crisis caused by terrorist attacks in New York on 11 September 2001.  The accent of public administration reforms was on efficiency and effectiveness of public institutions. Reforms were divided into deregulation and liberalization of public services, territorial decentralization, and regionalization with the strengthening of local government institutions and reform of central government administration. After the security crisis in 2001, financial crisis in 2008 and health crisis in 2020, the role of state institutions and public authorities in governing the state was redefined. The leading motives of general liberalization of public services, deregulation, and various forms of decentralization of public institutions abounded due to the new doctrinal approach of governmental organization. New strengthening of public authorities and public institutions became the new mainstream in the organization and functioning of the state. This paper analyzes how the role of the state can be modified due to the dynamics of social, political, and economic changes in society. New governmental reforms are contrary to earlier political and administrative measures, which include the strengthening of public institutions and concentration of public authorities. The government takes on a regulatory function in many aspects of social, political, and economic life. This situation leads to a new organization of the state, where public authorities take on a significant part of the responsibility to regulate various aspects of economic and social activities. At the focus of this paper will be how the dynamics of specific circumstances in society can affect the developing processes of the state and their public institutions. Those processes have economic, social, and political dimensions. The economic dimension includes regulatory measures on the market which contributes to development of the framework for economic development. The social dimension includes measures of social policy focused on improving the social position of citizens according to the economic development of society. The political dimension includes various aspects of security policy, with various protective measures in the community, which depends on the type of treatment for security of citizens.
Keywords: government administration, public institutions, dynamics of transition